Exciton states and optical properties of the CP26 photosynthetic protein. (February 2018) - Khokhlov, Daniil V.; Belov, Aleksandr S.; Eremin, Vadim V.
Graphical abstract: Highlights: The exciton Hamiltonian for the CP26 light-harvesting antenna has been constructed. Absorption, CD, and LD spectra of the antenna have been simulated. Possible roles of the chlorophylls within the antenna have been discussed. Abstract: The photosynthetic complex CP26, one of the minor antennae of the photosystem II, plays an important role in regulation of the excitation energy transfer in the PSII. Due to instability during isolation and purification, it remained poorly studied from the viewpoint of theoretical chemistry because of the absence of X-ray crystallography data. In this work, using the recently determined three-dimensional structure of the complex we apply the quantum chemical approach to study the properties of exciton states in it. Spectral properties, structure of exciton states and roles of the pigments in the complex and photosystem II are discussed.